2019
DOI: 10.4236/ojapps.2019.97046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and <i>In-Vitro</i> Antimicrobial Studies of M<sup>2+</sup>+ Complexes of <i>p</i>-Chlorophenyl-, <i>p</i>-Bromophenyl-Dithiocarbamates

Abstract: This study reports the synthesis of metal complexes of mixed ligands p-Chlorophenyl-, p-Bromophenyl-dithiocarbamates. The spectral properties of the metal complexes [Zn(II), Cd(II), Hg(II), Cu(II), Co(II) and Ni(II)] were obtained using the FTIR and UV/Vis spectroscopic techniques. Their antibacterial studies revealed that these complexes as well as the ligands could serve as possible antibacterial agents against pathogens. Melting point and solubility measurements were also carried out. It was observed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The work showed the copper(II) complex to exert no effect towards any of the microorganisms tested while the cobalt(II) complex exhibited the greatest activity [50,51]. A similar observation was made in the study of metal(II) complexes bearing mixed 4chlorophenyl-and 4-bromophenyldithiocarbamates, formulated as M(L 3 )(L 4 ) for M(II) = Co, Ni, Cu, Zn, Cd, and Hg, where the presence of the metal ion resulted in improved efficacy against selected bacteria (E. coli, S. mercescens, and S. aureus) compared with the free ligand [52]. However, the complexes exhibited weak to no activity towards the investigated fungi (T. viride and M. albicans).…”
Section: Transition Metal Dithiocarbamatessupporting
confidence: 61%
See 1 more Smart Citation
“…The work showed the copper(II) complex to exert no effect towards any of the microorganisms tested while the cobalt(II) complex exhibited the greatest activity [50,51]. A similar observation was made in the study of metal(II) complexes bearing mixed 4chlorophenyl-and 4-bromophenyldithiocarbamates, formulated as M(L 3 )(L 4 ) for M(II) = Co, Ni, Cu, Zn, Cd, and Hg, where the presence of the metal ion resulted in improved efficacy against selected bacteria (E. coli, S. mercescens, and S. aureus) compared with the free ligand [52]. However, the complexes exhibited weak to no activity towards the investigated fungi (T. viride and M. albicans).…”
Section: Transition Metal Dithiocarbamatessupporting
confidence: 61%
“…The authors suggested that in addition to the enhanced activity attributed to the presence of metals and the heteroaromatics, that is, benzisothiazolinate and saccharinate, the complexes with greater size (molecular weight) were found to exert better antimicrobial responses due to their greater permeability through the microbial cell wall [74]. In another study, El-said and colleagues reported a series of nickel(II) complexes of multifunctional, dianionic dithiocarbamates, that is, dithiocarbamates derived from amino acids, Ni(L [49][50][51][52][53] )(phen) 2 , as well as a dinuclear copper(II) complex formulated as [Cu 2 (L 51 )Br 2 (phen) 2 (H 2 O) 2 ]; these complexes were shown to be active towards bacteria (B. cereus, E. coli, and P. aeruginosa) and fungi (A. niger and T. roseum) [75].…”
Section: Transition Metal Dithiocarbamatesmentioning
confidence: 99%